The phylogeny and distribution of Wolbachia in two pathogen vector insects, Asian citrus psyllid and Longan psyllid - Ou, Da; Qiu, Jun-Hong; Su, Zheng-Qin; Wang, Lei; Qiu, Bao-Li (Frontiers in Cellular and Infection Microbiology, 2023)
Background Wolbachia is the most abundant bacterial endosymbiont among insects. It can play a prominent role in the development, reproduction and immunity of its given insect host. To date, Wolbachia presence is well studied within aphids, whiteflies and planthoppers, but relatively few studies have investigated its presence in psyllids. Methods Here, the infection status of Wolbachia in five species of psyllid, including Asian citrus psyllid Diaphorina citri and longan psyllid Cornegenapsylla sinica was investigated. The phylogenetic relationships of different Wolbachia lines and their infection density and patterns in D. citri and C. sinica from different countries was also examined. Results The infection rates of Wolbachia in D. citri and C. sinica were both 100%, and their sequencing types are ST173 and ST532 respectively. Phylogenetic analysis revealed that the Wolbachia lines in D. citri and C. sinica both belong to the Con subgroup of Wolbachia supergroup B. In addition, Wolbachia displayed a scattered localization pattern in the 5th instar nymphs and in the reproductive organs of both D. citri and C. sinica but differed in other tissues; it was highest in the midgut, lowest in the salivary glands and medium in both the testes and ovaries. Conclusion Our findings assist in further understanding the coevolution of Wolbachia and its psyllid hosts. Given that Wolbachia could play an important role in insect pest control and pathogen transmission inhibition, our findings may also provide new insights for development of control strategies for D. citri and C. sinica.